POSTMAGMATIC COOLING AND LATE CENOZOIC DENUDATION OF THE NORTH PATAGONIAN BATHOLITH IN THE LOS LAGOS REGION OF CHILE, 41°−42°15′S - Adriasola A.C.; Thomson S.N.; Brix M.R.; Hervé F.; Stöckhert B. (My University, 2006)
Zircon and apatite fission track (FT) thermochronology was applied to investigate the history of cooling and denudation of the Southern Andes between 41° and 42°15′S in relation to the late Cenozoic activity of the Liquiñe-Ofqui fault zone (LOFZ) and the northward migration of the Chile Triple Junction (CTJ). Fifty-six zircon and 51 apatite FT ages, plus 37 apatite confined track-length distributions were obtained mainly from plutonic rocks of the North Patagonian Batholith (NPB) in the main Andean Cordillera. Apatite FT ages and track lengths indicate a stage of rapid cooling at ~5--3 Ma along both sides of the LOFZ, whereas older Miocene ages with monotonous cooling histories were obtained further away from the fault. Zircon FT ages range from Cretaceous to Pliocene, with marked differences observed along and across the LOFZ. Three different types of temperature-time histories characterise the post-magmatic cooling of the NPB in the region: deep intrusions with moderate and steady cooling rates, intrusions in the upper crust with very slow cooling rates following a stage of initial rapid cooling, and rapidly cooled and exhumed shallow intrusions, the latter with younger ages towards the fault zone. The most prominent denudation episode along the LOFZ is late Miocene to Pliocene, coeval with plate tectonic reconstructions for the arrival and subduction of the Chile Rise beneath the Taitao Peninsula.
Keywords: SOUTHERN CHILEAN ANDES; LIQUIñE-OFQUI FAULT ZONE; FISSION TRACK THERMOCHRONOLOGY; ARC MAGMATISM; DENUDATION; Cretaceous; Pliocene; Miocene; Mesozoic::Cretaceous; Мезозой::Меловая; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен